Imagined and extended contact experiences and adolescent bystanders' behavioral intentions in homophobic bullying episodes - António, Raquel (2022)
Bystanders' helping interventions in bias‐based bullying are rare, although they have the potential to intervene on behalf of the victim and quickly stop the aggression. Two studies tested, experimentally, the impact of adolescents' imagined (Study 1, N = 113, Mage = 16.17) and extended contact experiences (Study 2, N = 174, Mage = 15.79) on assertive bystanders' behavioral intentions in the context of homophobic bullying, an under‐ researched but highly detrimental behavior that emerges mainly during early adolescence. Potential mediators (empathic concern, social contagion concerns, and masculinity/ femininity threat) were also examined. Results showed that female younger participants revealed more behavioral intentions to help victims of homophobic bullying when asked to imagine an interaction with an outgroup member (Study 1). Younger participants revealed less masculinity/femininity threat in the positive extended contact condition, and female participants revealed less empathic concern in the negative extended contact condition (Study 2). Overall, these findings identify specific conditions (e.g., younger females) where indirect contact interventions (i.e., extended and imagined) are likely to have a stronger impact. Age and sex differences were found to illustrate how adolescents vary in their behavioral intentions, empathic concern, and threat; and also highlight the need to further examine age and sex differences regarding responses to homophobic bullying episodes.